2001
DOI: 10.1093/humrep/16.2.277
|View full text |Cite
|
Sign up to set email alerts
|

Monthly variation in human semen quality in male partners of infertile women in the tropics

Abstract: The aim of the study was to determine whether there were significant 'seasonal' variations in the rhythm of sperm parameters (i.e. semen volume and sperm density) of men who reside in the tropics. A total of 7656 semen analysis results from the department of obstetrics and gynaecology of a tertiary general hospital was analysed. These samples were obtained as part of an initial screening for male partners of couples with problems trying to conceive who were attending a fertility clinic from 1991 to 1995. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 12 publications
0
14
1
Order By: Relevance
“…This discrepancy should be considered when comparing data of semen volumes between different laboratories. According to our comparison of the results from different Asian studies, the mean semen volumes of China (north/south/central), Thailand, Singapore and India were 3.0/2.9/2.4, 2.5, 2.4 and 2.5 mL, respectively 35 . In contrast, semen volume of the fertile Japanese men was 3.2 mL; 20 which is the highest value among the Asian men examined here.…”
Section: Review Of Reproductive Parameters In Asian Healthy Menmentioning
confidence: 57%
“…This discrepancy should be considered when comparing data of semen volumes between different laboratories. According to our comparison of the results from different Asian studies, the mean semen volumes of China (north/south/central), Thailand, Singapore and India were 3.0/2.9/2.4, 2.5, 2.4 and 2.5 mL, respectively 35 . In contrast, semen volume of the fertile Japanese men was 3.2 mL; 20 which is the highest value among the Asian men examined here.…”
Section: Review Of Reproductive Parameters In Asian Healthy Menmentioning
confidence: 57%
“…Although air conditions have improved recently, air quality is reportedly worse, and the PAH levels are higher in December in this city (CEPB 2007). Additionally, several reports have indicated that sperm quality is subject to seasonal changes because of temperature changes, the length of daylight, or ejaculatory frequency (Carlsen et al 2004; Chia et al 2001; Hansen et al 2010). The winter season in Chongqing sees mild weather with overcast conditions and average temperatures around 10°C.…”
Section: Discussionmentioning
confidence: 99%
“…Chia et al reported there were no significant month-to-month fluctuations in semen volume and sperm density among men who resided in the tropics [26], where there are minimal changes in temperature, unlike the seasonal variation of climate in the New England region. In our study, improved semen parameters in the spring may reflect spermatogenesis during the cold New England winter.…”
Section: Discussionmentioning
confidence: 99%